Maturation level in adolescents: effects on body composition and physical activity changes - Benítez-Porres, Javier; Alvero-Cruz, José Ramón; Moore, Justin B.; Álvarez-Carnero, Elvis (My University, 2016)
Background and aims: Longitudinal studies help move researchers closer to understanding determinants and mediators of maturation, physical activity (PA) and adiposity. The aim of this study was to longitudinally explore the influence of maturation on PA and adiposity changes in adolescents. Methods: Eighty healthy adolescents (42 girls and 38 boys) were followed over three academic years. A PA score was estimated using the Physical Activity Questionnaire (PAQ-A). Fat mass percentage (FMP) was assessed by anthropometric measurements. Sexual maturity was estimated by percentage of predicted adult stature and adolescents were classified into three changes groups: C0, change from on time to late maturation; C1, no change; C2, change from late/on time to on time/early maturation. A stepwise linear regression was conducted in order to estimate the predictors of PA and FMP changes. Results: An interaction between PA and maturation was statically significant (P<0.05). A non-significant trend was observed between three stages of change with a progressive reduction of FMP across the three stages of change in maturation level (C0 = 0.2752.70%; C1= -1.4901.10%; C2= -6.4172.57%; pairwise comparisons: C0 - C2 = 6.69%, P=0.081 and C1-C2 = 4.93%, P=0.080). Conclusions: Our results suggest that body composition changes observed during adolescence are not driven by changes in PA. PA alteration patterns were influenced by sex but not by maturation.
Keywords: Adolescencia; Adolescence; Maturity; PAQ-A